stepRNA: Identification of Dicer cleavage signatures and passenger strand lengths in small RNA sequences - Murcott, Ben; Pawluk, Rebecca J.; Protasio, Anna V.; Akinmusola, Ruth Y.; Lastik, Dominika; Hunt, Vicky L. (Frontiers in Bioinformatics, 2022)
The enzyme Dicer is a component of many small RNA (sRNA) pathways involved in RNA processing for post-transcriptional regulation, anti-viral response and control of transposable elements. Cleavage of double-stranded RNA by Dicer produces a signature overhanging sequence at the 3’ end of the sRNA sequence relative to a complementary passenger strand in a RNA duplex. There is a need for reliable tools to computationally search for Dicer cleavage signatures to help characterise families of sRNAs. This is increasingly important due to the rising popularity of sRNA sequencing, especially in non-model organisms. Here, we present stepRNA, a fast, local tool that identifies (i) overhang signatures strongly indicative of Dicer cleavage in RNA sequences, and (ii) the length of the passenger strand in sRNAs duplexes. We demonstrate the use of stepRNA with simulated and biological datasets to detect Dicer cleavage signatures in experimentally validated examples. Compared to currently available tools, stepRNA is more accurate, requires only sRNA sequence data rather than a reference genome, and provides information about other important features such as passenger strand length. stepRNA is freely available at https://github.com/Vicky-Hunt-Lab/stepRNA and is easily installable.